MyPainPal: Co-creation of a mHealth app for the management of chronic pain in young people. (2nd September 2021) - Cooke, Marie; Richards, Julianne; Tjondronegoro, Dian; Raj Chakraborty, Prithwi; Jauncey-Cooke, Jacqueline; Andresen, Elizabeth; Theodoros, Joanne; Paterson, Rebecca; Schults, Jessica; Raithatha, Bhavesh; Wilson, Susan; Alcock, Mark
ABSTRACT: Chronic pain is common in young people aged 10–14 years. Interdisciplinary, clinician-delivered treatments, while effective, are often criticized for failing to be readily accessible. Mobile health applications (mHealth apps) have been proposed as effective treatment adjuncts that address these challenges, while meeting the needs of tech-savvy young people. The objectives of this study were to co-create a mHealth app with consumers and health care professionals and evaluate the acceptability and feasibility of the resulting mHealth app (myPainPal). A phased, qualitative approach within a consumer engagement framework was employed. Interviews with young people ( n = 14), parents ( n = 12) and health care professionals ( n = 8) identified key health needs that formed the underlying structure of the myPainPal app. Testing showed that the app is an acceptable and feasible platform to facilitate young people's self-management of chronic pain. The myPainPal app has the potential to positively influence young people's experiences of chronic pain. Further testing in controlled settings is required.